Information technology and government-to business: what are the values derived? - Kassim, Erne Suzila; Hussin, Husnayati (2010)
The information and communication technology has not only formed a pressure to business organizations to engage in online trading, but combined with social pressure, these forces have also influenced the public sector to automate their interactions with other govermnent organizations and businesses; the process known as govermnent-to-business (G2B). The decision to automate public sector business processes is seen among others as a mean to improve transparency and service performance. However, despite the anticipated benefits, there still seem to be lack of research findings that have discussed on the values obtained from the use of the G2B system. Therefore, driven by the limited research understanding in the area, this study was undertaken to evaluate the values derived from the G2B system, measured as process efficiency, information quality, transparency and service performance among Malaysian federal govermnent agencies. The findings suggest the G2B system has indeed given significant evidences to the value achievement. Based on the findings, implication for future research is offered